Pengembangan Ketrampilan Siswa SMP Bina Insani Dan Pemberdayaan UMKM Desa Cibeuteung Muara - Araminta, Widyadhari Yumna; Adilah, Dzulkahfi Zaki; Farid, Muhammad; Rusdiah, Ratu; GS, R. Haryo Dewanto; Latifani, Arda Aprilia; Asari, Hafizh Ihsan; Satrio, Garin Ahmad; Rezaskov, Achmad Altariq; Amelia, Amelia; Maryama, Siti (Journal Of Human And Education (JAHE), 2025)
Digital skills, especially in the use of Microsoft Word, are very important for junior high school students. On the other hand, at the same time, MSMEs in Muara Village face difficulties in attracting a large number of consumers to buy their products, especially using social media. This study aims to improve students' Microsoft Word skills and provide effective marketing strategies using social media services for Micro, Small, and Medium Enterprises. The method used in this study is field training. All training participants are junior high school students and MSME collectors in the market. This training will discuss Computer skills further. This study is equipped with video documentation and presentations, as well as social media marketing strategies to increase product visibility. Data were collected through observation, interviewing and interviewing customers, conducting sales coefficient surveys before and after the training. The results of the study showed that students' skills in making more professional documents and efforts increased MSME sales by up to 30% in one month from the implementation of conducive marketing strategies. In conclusion, this study supports the important position of the interconnection between education and the business sector in increasing self-esteem, and provides insight into the benefits of skills training for students and small and medium enterprises in Muara Village.